2019
DOI: 10.15520/ijnd.v9i06.2594
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices of Kegel Exercise among Postnatal Women, in Al Madinah Al Munawarah, Saudi Arabia

Abstract: Background: Kegel exercise role in strengthening the pelvic floor muscle in the treatment of prolapse and urinary incontinence and improve mobility and relieves painAim; The study aims to assess the knowledge and attitude and practices of kegel exercise among postnatal women in Al Madinah Al Munawarh, Saudi Arabia. Study design: This study utilized descriptive quantitative cross-sectional study design.Study Setting:The study was conducted of the postnatal ward in Maternity and Children's Hospital in Al Madinah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 4 publications
3
15
1
Order By: Relevance
“…A similar study conducted in Taif city revealed that more than half of the study subjects were using contraceptives. [ 8 9 ] Whereas another study done in Al-Qassim measuring the awareness of use of contraceptives among Saudi women attending primary care centers showed a low level of knowledge. [ 10 ] Hence, the knowledge and practice of family planning varies in many regions of the Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study conducted in Taif city revealed that more than half of the study subjects were using contraceptives. [ 8 9 ] Whereas another study done in Al-Qassim measuring the awareness of use of contraceptives among Saudi women attending primary care centers showed a low level of knowledge. [ 10 ] Hence, the knowledge and practice of family planning varies in many regions of the Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…This study findings were in discordant with many other study results like Jawaher et al, Ibrahim et al, Alharqi et al, which media was the most common source reported for information of PNE. 6,11,12 This study findings may be attributed to the protocol of the tertiary care centre which is having the practice of getting physiotherapy consultant for all postnatal mother delivered in the hospital and also the consultants and nursing staffs will emphasize the importance of PNE during antenatal and postnatal visit.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast to the other studies Jawaher et al, Alharqi et al, who have reported positive association between women's education and knowledge about PNE, this studies report suggest that there was no significant correlation between any socio demographic character with knowledge, attitude and practice of PNE. 6,12 This may be due to nature of this study population which had more than 50% educated and all of them either from urban or semi urban area and protocol of the health system had the positive influence on adherence to PNE which was shown by the positive attitude almost by all patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations